2011
DOI: 10.1097/mcg.0b013e3181e12511
|View full text |Cite
|
Sign up to set email alerts
|

Mild Alcohol Consumption is Not Associated With Increased Fibrosis in Patients With Chronic Hepatitis C

Abstract: Mild alcohol use does not seem to adversely affect the severity of fibrosis in patients with chronic HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Despite the likely contributions of alcohol to hepatic fibrosis, the effect of subclinical/moderate alcohol consumption in the setting of superimposed liver injury is not well understood. There are conflicting findings regarding the impact of moderate alcohol consumption on the progression of chronic liver diseases, particularly from observational studies in patients with non-alcoholic chronic liver disease [31][33]. Results between these different studies are difficult to compare due to variation in the definition and quantification of alcohol intake, as well as other dietary confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the likely contributions of alcohol to hepatic fibrosis, the effect of subclinical/moderate alcohol consumption in the setting of superimposed liver injury is not well understood. There are conflicting findings regarding the impact of moderate alcohol consumption on the progression of chronic liver diseases, particularly from observational studies in patients with non-alcoholic chronic liver disease [31][33]. Results between these different studies are difficult to compare due to variation in the definition and quantification of alcohol intake, as well as other dietary confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of ongoing alcohol consumption on "all-stages of fibrosis" in HCV-related chronic hepatitis, as defined before the DAA era, is controversial. 87,88 In patients with advanced liver fibrosis, alcohol increases the risk of liver events. In a prospective study conducted in 74 patients with HCV-related cirrhosis, light to moderate alcohol intake and a lack of viral eradication were associated with the risk of HCC (HR for alcohol consumption: 3.43; 95% CI 1.49-7.92; p = 0.004).…”
Section: Assessment Of Portal Hypertensionmentioning
confidence: 99%
“…Hezode et al initially reported a progressive increase in histologic severity and fibrosis in relation to the amount of alcohol intake in chronic HCV infection [59,70]. However, in a similar cohort of 857 patients, the degree of fibrosis was independent of mild-moderate alcohol consumption [71]. A similar negative effect is expected to occur with hepatitis B infection, but also in this condition conflicting data have been reported [72], as well as in storage defect disease [73].…”
Section: Cirrhosis By Blood Tests and Clinicalmentioning
confidence: 97%